2022
DOI: 10.1111/jocs.17218
|View full text |Cite
|
Sign up to set email alerts
|

The potential function of SP1 and CPPED1 in restenosis after percutaneous coronary intervention

Abstract: Objectives Impacts of molecular pathways have been discussed recently on restenosis after percutaneous coronary intervention (PCI). Hence, this study aimed to explore the impact of calcineurin‐like phosphoesterase domain containing 1 (CPPED1) and specificity protein 1 (SP1) on restenosis after PCI. Methods A carotid balloon injury rat model was established, followed by western blot analysis of SP1 and CPPED1 expression in carotid artery (CA) tissues. After SP1 and CPPED1 were overexpressed, the neointimal hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
0
0
Order By: Relevance
“… 76 Moreover, it has been reported that Sp1 is lowly expressed in the model rats with carotid balloon injury, and Sp1 overexpression reduces injury-induced neointimal formation and restenosis rate. 77 Therefore, findings from the study and previous studies clearly infer a functional role for TGFβ1/Sp1/SNHG18 signal axis in controlling and sustaining VSMC contractile phenotype as well as in preventing injury-induced adverse arterial remodelling.…”
Section: Discussionsupporting
confidence: 55%
“… 76 Moreover, it has been reported that Sp1 is lowly expressed in the model rats with carotid balloon injury, and Sp1 overexpression reduces injury-induced neointimal formation and restenosis rate. 77 Therefore, findings from the study and previous studies clearly infer a functional role for TGFβ1/Sp1/SNHG18 signal axis in controlling and sustaining VSMC contractile phenotype as well as in preventing injury-induced adverse arterial remodelling.…”
Section: Discussionsupporting
confidence: 55%
“…Multiple factors have been implicated in the science and mechanism of coronary artery restenosis after PCI such as endothelial progenitor cells (EPCs), Specificity Protein 1 (SP1), Calcineurin-Like Phosphodiesterase Domain containing 1 (CPPED1), medication non-compliance (Statins, and renin-angiotensin-aldosterone system blockers reduce in-stent restenosis), high levels of HB-EGF, interleukin-10 and interleukin-18, and sedentary lifestyle [1,[6][7][8][9][10]. A study also argued there may be an association between the occurrence of ISR and anemia thus recommending that anemia should be assessed at the follow up clinic visits [9].…”
Section: Introductionmentioning
confidence: 99%